The Effect of Foot Massage and Warm Footbath with Kencur Aromatic (Kaempferia galanga) on Foot Edema among Pregnant Women - Bunga Tiara Carolin; Cholisah Suralaga; Alya Salmawati (KHD Production, 2023)
Foot edema or swelling is found in about 80% of pregnant women in the third trimester; it occurs due to uterine pressure which inhibits venous return, and the pull of gravity which causes greater fluid retention. The incidence of edema at the Nagrak Health Center, Cianjur Regency, in May 2021 was 20.9%. Management of foot edema can be done in a non-pharmacological way, one of which is a foot massage and warm footbath with mixed with kencur (Kaempferia galanga) aromatic. The objective was to determine the effect of foot massage and warm footbaths with kencur aromatic on foot edema among pregnant women at the Nagrak Health Center, Cianjur Regency. This research was a quasi-experimental study using one group pretest and posttest design. The sample was 20 respondents. The sampling technique used was purposive sampling. The instrument was the SOP and the pitting scale observation sheet. The data normality test using the Shapiro Wilk found that the data were not normally distributed, so the data analysis used the Wilcoxon test. The results were average degree of foot edema before the intervention was 3+ and the average after the intervention was 1+. Based on the Wilcoxon test, the result of the 2-tailed sign with p-value=0.000 (p<0.05), then statistically there was a significant reduction of foot edema between before and after foot massage and warm footbath with kencur aromatic performed among third-trimester pregnant women. The conclusion was that there was an effect of foot massage and a warm footbath with kencur aromatic on foot edema among pregnant women at the Nagrak Health Center, Cianjur Regency. The suggestion is expected that pregnant women and health workers can practice foot massage and warm foot baths with kencur aromatic to reduce foot edema.